2016
DOI: 10.1515/mper-2016-0030
|View full text |Cite
|
Sign up to set email alerts
|

Smart Product Design and Production Control for Effective Mass Customization in the Industry 4.0 Concept

Abstract: The paper presents a general concept of smart design and production control as key elements for efficient operation of a smart factory. The authors present various techniques that aid the design process of individualized products and organization of their production in the context of realization of the mass customization strategy, which allows a shortened time of development for a new product. Particular attention was paid to integration of additive manufacturing technologies and virtual reality techniques, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
144
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(149 citation statements)
references
References 20 publications
0
144
0
5
Order By: Relevance
“…A virtual system is used to monitor and control its physical aspect, which sends data to update its virtual model in real time [5]. A virtual system enables the implementation of designs, creating digital prototypes that are very similar to the real ones [42].…”
Section: Design Principles Of a Smart Factorymentioning
confidence: 99%
See 1 more Smart Citation
“…A virtual system is used to monitor and control its physical aspect, which sends data to update its virtual model in real time [5]. A virtual system enables the implementation of designs, creating digital prototypes that are very similar to the real ones [42].…”
Section: Design Principles Of a Smart Factorymentioning
confidence: 99%
“…This system provides real-time tracking and an analysis of historical performance. Zawadzki and Zywicki [42] suggested a new method of designing a product in smart factories that combines virtual reality and rapid prototyping. Veza et al [83] suggested an MCDM approach to manage the virtual production network in the selection of production partners.He et al [84] suggested an algorithm to manage the storage space of flash memory aimed at optimizing the performance of cloud computing.…”
Section: Control Systemsmentioning
confidence: 99%
“…If one of these factors is not met, the idea of mass production individualisation will most likely be unfeasible. To achieve this, effective data processing technology is essential [15].…”
Section: Possibilities Of Using Big Data Analysis In Industrymentioning
confidence: 99%
“…The VR has also plenty of applications in medicine and biomedical engineering [10,11] and general education [12]. VR, as well as Augmented Reality (AR), plays an important role in Factories of the Future, within the Industry 4.0 concept [13,14].…”
Section: Introductionmentioning
confidence: 99%